Spawning, Overwintering and Summer Feeding Habitats Used by Anadromous Arctic Char (Salvelinus alpinus) of the Hornaday River, Northwest Territories, Canada - Harwood, Lois A.; Babaluk, John A. (ARCTIC, 2014)
Radio telemetry and t-bar tagging were used to locate sites used by Hornaday River Arctic char (Salvelinus alpinus) for overwintering, spawning, and summer feeding. Thirty char, 21 in August 1995 and nine in July and August 1999, were captured, radio-tagged, and released back into the Hornaday River. Tracking was done over 14 months in 1995 – 96 and over three months in 1999, using either aircraft (10 flights) or snowmobiles traveling on the river ice in winter (7 trips). Of 12 radio-tagged char that were relocated during winter 1995 – 96 and not caught in the 1995 upstream migration fall fishery, 11 (92%) ultimately overwintered in the reach of the Hornaday between Coalmine and Akluk Creek; three of these did so in consecutive years. This area is characterized by groundwater inputs and deep pools (> 2 m) that do not freeze to the riverbed in winter. Another important overwintering site was found in a similarly deep channel on the west side of the Hornaday River estuary, where half of the char radio-tagged in fall 1999 spent the winter of 1999 – 2000. Spawning locations were discerned through circumstantial evidence from the movements of three radio-tagged fish over entire annual cycles. The locations that were indicated as spawning habitat were all in the main stem of the Hornaday River, in deep (> 2 m), groundwater-fed pools between Coalmine and Akluk Creek. Fourteen percent of 239 char t-bar tagged at Pearce Point in July – August 1997 were caught at the mouth of the Hornaday River, on average within 25 days of tagging, which indicates that the nearshore area of Pearce Point, characterized by upwelling and enhanced productivity, is an important summer feeding area for this stock. This identification of overwintering, spawning, and summer feeding habitats contributes to an emerging list of areas for which it would be prudent to monitor habitat quality, change, and integrity given contemporary changes in climate and the potential for near-future anthropogenic activities in this watershed. La ...